2022
DOI: 10.1093/plphys/kiac223
|View full text |Cite
|
Sign up to set email alerts
|

Pit characters determine drought-induced embolism resistance of leaf xylem across 18 Neotropical tree species

Abstract: Embolism spreading in xylem is an important component of plant drought resistance. Since embolism resistance has been shown to be mechanistically linked to pit membrane characters in stem xylem, we speculate that similar mechanisms account for leaf xylem. We conducted transmission electron microscopy to investigate pit membrane characters in leaf xylem across 18 Neotropical tree species. We also conducted gold perfusion and polar lipid detection experiments on three species covering the full range of leaf embo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…At the pit level, Clematis should therefore be somewhat more susceptible to embolism than Fraxinus americana . Moreover, there is experimental evidence for a relationship between embolism resistance and the pit membrane diameter-to-thickness ratio ( Levionnois et al., 2021 ; Levionnois et al., 2022 ), suggesting that the deflection resistance of pit membranes may affect embolism propagation. Yet, it remains unclear how pit membrane thickness of fully hydrated, non-shrunken pit membranes may affect its elasticity modulus.…”
Section: Discussionmentioning
confidence: 99%
“…At the pit level, Clematis should therefore be somewhat more susceptible to embolism than Fraxinus americana . Moreover, there is experimental evidence for a relationship between embolism resistance and the pit membrane diameter-to-thickness ratio ( Levionnois et al., 2021 ; Levionnois et al., 2022 ), suggesting that the deflection resistance of pit membranes may affect embolism propagation. Yet, it remains unclear how pit membrane thickness of fully hydrated, non-shrunken pit membranes may affect its elasticity modulus.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike T PM , Levionnois et al (2022) found pit membrane diameter ( D PM ) and the ratio between maximum pit membrane thickness to pit membrane diameter ( T PM / D PM ) to be well correlated with P 50 at the species level for non-vestured pit species. This may suggest that, unlike T PM , D PM and T PM / D PM might not exhibit a large variation within species.…”
mentioning
confidence: 82%
“…E, Scanning electron microscope (SEM) image of hazelnut ( Corylus avellana ) showing a “single layer” of a pit membrane and large, artificial pores, which does not represent an intact pit membrane under natural conditions. F, TEM image showing penetration of gold particles of different sizes into a pit membrane (outlined by blue lines) of camphor tree ( Cinnamomum camphora ), that is, a method used by Levionnois et al (2022) to estimate pore constriction size. The perfusion direction of 5, 10, 20, and 50 nm particles was from right to left, with small particles going deeper into the membrane than larger ones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although xylem cavitation and embolism are easily observed in plants, the mechanics of xylem hydraulic failure processes in vivo remain a topic of active study in plant physiology (see Venturas et al, 2017 for a review). Recently, pit membrane characteristics (i.e., pore constrictions and pit membrane thickness) have been implicated as a primary mechanism in the mechanics of xylem hydraulic failure (Thonglim et al, 2021;Avila et al, 2022;Levionnois et al, 2022), making them an obvious target for predictive modeling. However, pit membranes are rarely preserved in the fossil record.…”
Section: Xylem Physiology From Fossils: Model Backgroundmentioning
confidence: 99%